Cedera Olahraga dan Layanan Fisioterapi pada Gangguan Minimal pada Atlet Paralimpik Indonesia di Asean Para Games Kamboja 2023 - Namira Mutia Khanza; Suryo Saputra Perdana (UNIB Press, 2025)
ASEAN Para Games is the largest disability sports competition in Southeast Asia. It is routinely held every two years. This study aims to identify sports injuries and physiotherapy services for minimal impairment in Indonesian Paralympic athletes during the ASEAN Para Games Cambodia 2023. The method was a retrospective descriptive epidemiological study with a cross-sectional approach and secondary data from NPC Indonesia. The population came from Indonesian Paralympic athletes who participated in the 2023 ASEAN Para Games, a total of 268 people. At the same time, the sample used was 174 athletes who suffered injuries and received physiotherapy services. Qualitative frequency analysis showed that limb deficiency was the most common impairment receiving physiotherapy services (42.5%, n=74). Of the 12 sports, Para Athletic was the most common sport in which physiotherapy services were received (77%, n=57). The knee and shoulder regions were the most commonly injured (20.6%, n=36). The massage gun was the most common physiotherapy modality, used 70 times out of a total of 1,498 times for all modalities. Services at the medical center clinic had the most follow-up status with 42 people, and receiving services in the field had the most resolved status with 61 people. This study provides valuable insights into injury patterns, medical admissions, and physiotherapy services during the ASEAN Para Games Cambodia 2023, besides highlighting the importance of tailored physiotherapy interventions in supporting the recovery of athletes during major Para sports events.